Assessment of Physical, Psychosocial, and Social Impact On Psychotic Substance Abusers And Their Families (International Journal of Biomedical Research, 2018)
The present study aims to assess social, psychological, and physical impact on substance abusers and their family so as to formulates effective polices and strategies to control the implications and health hazards of psychotic substance abuse.A total of 850 IPD hospitalized patients, using multiple psychoactive substances were selected from De-addiction centers of Punjab state and were personally interviewed by the author of this article to collect the information regarding the prevalence, distribution, and interrelations of variables within study population and recorded in self-structured questionnaire, prepared after reviewing the related studies to access physical, psychological and social problems/impact